Intercalation of psoralen into DNA of plastid chromosomes decreases late during barley chloroplast development. - Davies, J P (1991)
We have used a DNA crosslinking assay to measure intercalation of the psoralen derivative HMT (4'-hydroxymethyl-4,5',8-trimethylpsoralen) into barley (Hordeum vulgare) plastid chromosomal DNA during chloroplast and etioplast development. Intercalation into DNA in intact plastids in vivo and in plastid lysates in vitro shows that chromosomal DNA in the most mature chloroplasts intercalates HMT less efficiently than DNA in younger chloroplasts. In contrast, there is no change in HMT intercalation during etioplast differentiation in the dark. Our results also show that DNA in higher plant plastid chromosomes is under superhelical tension in vivo. The lower susceptibility to HMT intercalation of DNA in the most mature chloroplasts indicates that late during chloroplast development the superhelical tension or the binding of proteins to the DNA or both change.